The Analisis Nilai Tambah Bonggol Pisang (Musa paradisiaca L.) Menjadi Kerupuk Bongsang Pada UKM Abopink Di Desa Pringgacala Kecamatan Karangampel Kabupaten Indramayu - Pungky, Rinky; Supriyadi, Supriyadi; Laila, Fadhillah (Agri Wiralodra, 2024)
The purpose of this study was to (1) the added value of the banana corm processing business into bongsang crackers in UKM ABOPINK; and (2) to determine the value-added ratio of banana corm processing business becoming bongsang crackers at UKM ABOPINK. The research method used was a survey method, and the research design was a descriptive survey. Determination of the sample using purposive sampling technique, namely purposive sampling. Analysis of the data used in this study using added value analysis with the Hayami method. Based on the results of this study, the bongsang cracker processing business at UKM ABOPINK Pringgacala Village, Karangampel District, Indramayu Regency in 2020. UKM ABOPINK produces bongsang crackers with 1 package, which is a package containing 100 grams. With an added value of IDR. 40.905,50 with an added value ratio of 77,92% means that the added value is high in one production process.